2007
DOI: 10.1007/s12105-007-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

p63 Immunohistochemistry Differentiates Salivary Gland Oncocytoma and Oncocytic Carcinoma from Metastatic Renal Cell Carcinoma

Abstract: Metastatic renal cell carcinoma (RCC) can pose diagnostic challenges in the head and neck often resembling benign and malignant oncocytic lesions. Immunohistochemical panels have been reported to help with this differential but are not entirely specific or sensitive. We have noticed that p63 routinely stains salivary gland oncocytomas but not metastatic RCC. Nineteen oncocytomas, 9 cases of oncocytosis, 9 oncocytic carcinomas and 16 head and neck metastatic RCC were studied. Morphologic features evaluated were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 31 publications
(36 reference statements)
0
44
0
1
Order By: Relevance
“…The nuclei are larger and more atypical than HCCC, there is never squamous differentiation, and the dual stroma of HCCC is lacking. In addition, RCC never expresses p63 [17], which is almost always expressed in HCCC [9].…”
Section: Metastasesmentioning
confidence: 97%
“…The nuclei are larger and more atypical than HCCC, there is never squamous differentiation, and the dual stroma of HCCC is lacking. In addition, RCC never expresses p63 [17], which is almost always expressed in HCCC [9].…”
Section: Metastasesmentioning
confidence: 97%
“…In contrast to oncocytoma, there is no 1 3 dominant encapsulated lesion. Clear cell predominance may mimic the appearance of metastatic renal cell carcinoma, though nodular oncocytic hyperplasia does not show the hemorrhage or vascularity typically seen in renal cell carcinoma [19]. Lymphoepithelial lesions are pathognomonic for lymphoepithelial sialadenitis that is seen in Sjögren syndrome [20].…”
Section: Remaining "Other Epithelial Lesions"mentioning
confidence: 99%
“…It also stains the germinative cells of the secretory portion of sebaceous glands [54]. In a recent paper, p63 stained all sebaceous and NSLs, 11 and 7, respectfully [21], while a separate study found that all 16 metastatic renal cell carcinomas were negative for this antibody [55]. In addition, three primary sebaceous carcinomas of the skin in several recent studies also stained with p63 [54,56,57].…”
Section: Differential Diagnosismentioning
confidence: 94%